2015
DOI: 10.1016/j.egypro.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Economy of Heat Cost Allocation in Apartment Buildings

Abstract: Space heating cost allocation according to actual consumption can be one possible solution for saving energy as residents are more motivated to regulate indoor air temperature. Introduction of heat cost allocators is a technique which can be used to ensure that the consumer pays only for the heat supplied to him. Installation of allocators increases the motivation of inhabitants to regulate indoor temperatures and thereby reduce heat consumption. Nevertheless, different criterions need to be taken into account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
2
12
0
Order By: Relevance
“…These results are consistent with the results given by Ziemele et al (2015) who report that the apartments located on the top and bottom floors of a building have more heat loss than the other floors. When floor level factor is considered along with building age, it is seen that the ground floors in new building pay 100-199 TL (38.3%) whereas in buildings that are aged 30 or over, the ground floors pay 300-3999 TL (31.5%).…”
Section: Figure 6 State Of the Rcbn Model After Propagation Of The Evidencessupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with the results given by Ziemele et al (2015) who report that the apartments located on the top and bottom floors of a building have more heat loss than the other floors. When floor level factor is considered along with building age, it is seen that the ground floors in new building pay 100-199 TL (38.3%) whereas in buildings that are aged 30 or over, the ground floors pay 300-3999 TL (31.5%).…”
Section: Figure 6 State Of the Rcbn Model After Propagation Of The Evidencessupporting
confidence: 93%
“…Kazanasmaz et al (2014) examined the relation between architectural considerations and energy performance of the buildings in Izmir, Turkey and they made suggestions to predict the level of energy performances of the buildings in the early design phase. Ziemele et al (2015) studied the economy of heat cost allocation in apartment buildings in Riga, Latvia and suggested a model to fairly allocate the heating costs in each apartment. Wessels (2015) stated that the energy consumption of the buildings built in the Netherlands before 1970 was very high and these buildings constituted approximately 12.5% of the buildings in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Each apartment needs different amount of heat in order to ensure comfort conditions; therefore, it is necessary to introduce additional criteria for the assessment of heat consumption in order to prevent the unfair allocation of heat costs. These criteria are taken into account in Module 3, using certain assumptions (Module 4), determining the heat cost for each apartment in accordance with the method of heat cost allocation (Ziemele, 2015). Studies in Germany have shown a 10 %-40 % decrease in heat consumption if the apartments are equipped with individual heat meters.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The method of measurement with heat cost allocators should also take into account the heat loss through the building envelope and heat gain, the heat flow from the riser pipes; it is necessary to recalculate the radiator assessment factor and the heat transfer between the apartments, as well as the fixed and variable proportion of the heat content each month, while the fixed consumption consists of the heat gain from uncovered heating network pipes in apartments and heat consumption in common areas (Ziemele, 2015).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The main factor behind the increased consumption in most cases is the unfavorable location of the apartment in the building. The difference in energy requirements related to the position of the flat in the building is broadly discussed within the literature [10,[12][13]28]. -98% -88% -78% -68% -58% -48% -38% -28% -18% -8% 3% 13% 23% 33% 43% 53% 63% 73% 83% The share of apartments with higher heat energy consumption in different cities is generally below 20% in all cities, except Karlovac.…”
Section: Specific Energy Requirements and Savings After Installing Hcasmentioning
confidence: 99%